Travel Literature as Cultural Mediation: A Postcolonial Reading of Robert Frost’s “The Road Not Taken” - Dewan, Motikala Subba (The Outlook: Journal of English Studies, 2025)
Travel literature functions both as a mirror reflecting personal experiences and as a window offering insights into diverse cultures. While earlier scholarship has often framed travel narratives primarily as vehicles of personal growth, there remains a significant gap in understanding how travel literature actively mediates cultural exchange and challenges entrenched perceptions shaped by colonial histories. This paper explores travel literature as a dynamic medium for fostering cultural understanding and transformation. It analyzes how travel narratives document encounters with unfamiliar cultures, reshaping worldviews and questioning preconceived notions. Using Robert Frost’s poem “The Road Not Taken” as a central metaphor for navigating unfamiliar cultural paths, this study employs Homi K. Bhabha’s postcolonial concepts of hybridity and cultural negotiation alongside Richard Hoggart’s perspectives on cultural identity and transformation as its theoretical framework. Through these critical lenses, travel literature emerges not merely as personal storytelling but as a form of cultural mediation that crosses boundaries, cultivates empathy, and generates new cultural perspectives. This paper calls for a reevaluation of travel literature as a dynamic force capable of challenging the status quo and promoting global cultural awareness. By encouraging readers to traverse unfamiliar territories, both literal and metaphorical, travel literature broadens worldviews and inspires novel understandings of the world.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />